FUNGSI DAN MAKNA KANARAZU, KITTO DAN ZETTAI DALAM OMIK MIDORI NO HIBI VOLUME 1-7 KARYA KAZURO INOUE - Dwikarmawan Sudipa, Made Henra (Humanis; Volume 15. No.3. Juni 2016, 2016)
This research describes the functions and contextual meaning of adverbs kanarazu, kitto and zettai found in Japanese comics entitled Midori no Hibi volume 1-7 written by Kazuro Inoue. The obtained data were analyzed using descriptive analysis method. This research applied the theory of syntax by Verhaar (2010) and theory of contextual meaning by Pateda (2001). There is one function of kanarazu, three functions of kitto and two functions of zettai. Contextual meaning from these adverbs were influenced by formality and speaker’s mood contexts.
Keywords: adverbs, function, contextual meaning